Model analizy conjoint w ocenie oferty ubezpieczeń od ryzyka do kredytu hipotecznego - Tarka, Piotr; Żuraw, Paweł (Model of Conjoint Analysis in the Evaluation of the Offer of Risk Insurance to Mortgage Credit, 2008)
Hereby article has been written on the ground of research results carried out within the quota sample consisting of Bank Zachodni WBK customers. The goal of research was to determine the attraction level and the point of view from prospective and actual customers in the sphere of particular insurance packages associated with risk in repayment mortgage. In order to attain this goal the authors used multidimensional model of conjoint analysis. This model has allowed to establish and explain complete utility banking product by comparison with its partial utility. Attributes concerning particular offers being presented before and assessed by respondents were targeted with the purpose of getting the best of their preferences arrangement to offers and attributes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 493-501